Educa????o f??sica escolar na fronteira Brasil-Bol??via: desafios e dilemas interculturais - Golin, Carlo Henrique (2017)
The present work was developed in the city of Corumb?? in the state of Mato Grosso do Sul (Brazil), a frontier site that interacts with Bolivia. In this place there is the permanent presence of different ethnicities that transit and perpass that territory. Before this reality and its complex frontier nuances (Brazil-Bolivia), the School Physical Education is discussed in this thesis, linked to the themes such as education, cultural diversity, interculturality, ethnicity, ethnocentrism, sport and body. It should be emphasized that the region studied is influenced by the various events (macro and micro) of the social, cultural, political and economic fields, creating a mosaic of approximations, exchanges, difficulties, frictions and constraints that permeate human relations at the border, which tend to be valued, stressed and/or shared by the people who live in that place. Thus, the present study seek to understand the School Physical Education in a frontier territory, that undergoes diverse influences of its own context, resulting from national and international laws, cultural, political/diplomatic, economic, social, ethnic factors. Considering processes of approximations and prejudices existing in the region, the general objective was to examine the ethnic aspects that permeate the pedagogical actions of the School Physical Education discipline, especially observing how teachers and students describe ??? the latter from different ethnicities and identities (in some cases hybrids) ??? on corporal practices in a border school. In methodological terms the research had as background the ethnography, especially considering the complexity of articulation between the Physical Education area and the different aspects of the frontier under study. We interviewed seven teachers and 20 students (Brazilian-Bolivians) from a municipal public school (CAIC), particularly close to the border (Brazil-Bolivia) and with a greater number of students living in Bolivia who do the pendulum movement to study in Brazil. Field survey data were collected through interviews that were previously structured (script) and analyzed qualitatively (discourse analysis). Subsequently, with the information of all interviewees, it was possible to compare intragroup data (teacher X teacher / student X student) and also between groups (teachers X students). We obtained, from this, the convergences and divergences between the discourses of the respondents, particularly on the issues related to intercultural education and the sociocultural aspects in the conduction of the Physical Education discipline in the frontier region. The data analyzed indicate that there is potential in the area to collaborate in overcoming possible discriminatory processes among students, also projecting new educational issues/concerns for Physical Education teachers and other undergraduate courses, especially for those who want to consider the intercultural education in regions with international border integration.